Factors Predicting Family Caregiver Burden in Older Adults with Stroke Patients in Wenzhou, China - Cai, Yuanyuan; Toonsiri, Chanandchidadussadee (วารสารคณะพยาบาลศาสตร์ มหาวิทยาลัยบูรพา, 2025)
This study aimed to characterize the burden level experienced by family caregiver and to investigate the factors predicting family caregiver burden in older adults with stroke in Wenzhou, China. A simple random sampling method was used to recruit the sample of 101 patient-caregiver dyads in the Second Affiliated Hospital of Wenzhou Medical University. Research instruments included the Demographic questionnaire, the Zarit Burden Interview Scale, the Modified Barthel Index scale, A New Post-Stroke Depression Scale, Chinese version of the Social Support Rating Scale. Descriptive statistics and stepwise multiple regression analysis were used to analyze the data. The results revealed that the sample had mean score of the family caregiver’s burden at a moderate level (M=44.97, SD=18.43). The significant predictors of burden for family caregivers of older adults with stroke were activities of daily living (β= -0.400, P<0.001), social support (β= -0.353, P<0.001), and post-stroke depression (β= 0.188, P=0.039). The caregiver-patient relationship: cousin (β= -0.177, P=0.017) was a significant predictor, as opposed to being a spouse or child. These predictors could together explain 49.7% of the variance in burden for family caregivers of older adults with stroke. (R2= 0.497, p < 0.001) Activities of daily living, post-stroke depression, social support, and caregiver-patient relationship are the significant predictors of burden for family caregivers of older adults with stroke. The results of this study serve as a reference for healthcare personnel should be developing the intervention based on the activities of daily, strengthening social suport systems, enhancing stroke outcomes, and improving the caregiver-patient relationship, thereby effectively reducing the burden of family caregivers.